Digital Twin for management of water resources in the Limpopo River Basin: a concept - Garcia Andarcia, Mariangel; Dickens, Chris; Silva, Paulo; Matheswaran, Karthikeyan; Koo, Jawoo (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2024)
A Digital Twin is a virtual representation of an object or system that spans its lifecycle, is updated from real-time data, and uses simulation, machine learning and reasoning to help decision making. The use of Digital Twins to aid decision-makers to make realtime decisions in complex systems is a growing field, with large potential for water system management. The CGIAR Initiative on Digital Innovation is developing a prototype Digital Twin for the Limpopo River Basin in close combination with stakeholders, to enable better management and conservation of this imperilled natural resource upon which millions of people depend. The Digital Twin will provide an attractive and easy-to-use interface for users to intuitively understand large volumes of data and modelling results for timely management decisions, and to simulate the impact of these decisions on the complex river basin ecosystem before they are put into action. This includes an artificial intelligence (AI) tool to interrogate and visualize key actionable data and forecasts. It will be developed in a phased approach according to stakeholder priorities.